PENDIDIKAN AHKLAK DALAM PRESFEKTIF ISLAMTANTANGAN DAN SOLUSIDI ERA MILENIAL - Wardiah; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2026)
Moral education is a fundamental aspect in islam which aims to shape individual personalities in accordance with moral and spiritual values. In the millennial era, moral education faces complex challenges due to technological developments, globalization, and cultural changes. Modern lifestyles that tend to be individualistic, the influence of sosial media, and unlimited access to information often shift the priorities of moral education. This article aims to explore these chellenges and offer practical and cotextual solutions. This research approach is qualitative with a literature study method on clasiccal and contemporary islamic sources. The results of the analysis show that moral learning needs to be integrated with digital technology to reach the millennial generation. The roles of families, schools an communities are key in creating a sustainable moral education ecosystem. Solutions include strengthening the curriculum based of islamic volues, using digital media as a means of da’wah, and cultivating morals through example. Apart from that, revitalizing the function of mosques and religious based communities is also needed to strengthen character formation. This article emphasizes the importance of collaboration between various parties in facing the challenges of the millennial era, so that the young generation can grow up with moral values that are strong and relevant to the dynamics of the times.